2013
DOI: 10.1155/2013/871528
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of pH Value in the Synthesis of Titanate Nanotubes‐Loaded Manganese Oxides as a Superior Catalyst for the Selective Catalytic Reduction of NO with NH3

Abstract: Titanate nanotubes (TNTs) synthesized by hydrothermal method were increasingly used as the catalyst support for the selective catalytic reduction (SCR) of NO with ammonia. This paper reports the critical process of postwashing to prepare satisfactory TNTs for the uses of SCR catalysts. Herein, alkaline TNTs (TNTs-AL), acidic TNTs (TNTs-AC), and neutral TNTs (TNTs-NE) were synthesized by controlling washing pH value. When these TNTs were utilized as the catalyst supports for manganese oxides (Mn/TNTs-AL, Mn/TNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Ag-doped TiO 2 nanofibers were shown to have increased photodegradation of 2-chlorophenol under UV treatment [111]. In addition, titanates, the inorganic compounds of titanium oxide, were described for the elimination of pollutants [112]. TiO 2 nanoparticles are also used as a catalyst to convert harmful sulphur dioxide (SO2) from atmosphere into sulphur through a chemical reaction.…”
Section: Metal-based Nanomaterialsmentioning
confidence: 99%
“…Ag-doped TiO 2 nanofibers were shown to have increased photodegradation of 2-chlorophenol under UV treatment [111]. In addition, titanates, the inorganic compounds of titanium oxide, were described for the elimination of pollutants [112]. TiO 2 nanoparticles are also used as a catalyst to convert harmful sulphur dioxide (SO2) from atmosphere into sulphur through a chemical reaction.…”
Section: Metal-based Nanomaterialsmentioning
confidence: 99%
“…Titanium oxide materials are used for the removal of contaminants. Chen et al [74] have demonstrated the fabrication of a wide range of titanate nanotubes (TNTs), such as acidic, basic, and neutral nanotubes, through the hydrothermal method of nanomaterial production. Rasalingam et al, [75] recorded the separation method of TiO2-SiO using the silica source from bamboo materials.…”
Section: Environmental Remediation: Nanoparticles Can Be Used To Clea...mentioning
confidence: 99%
“…In addition to titanium oxide materials, titanates (i.e., inorganic compounds of titanium oxide) have also been reported for the removal of contaminants. For instance, Chen et al [ 35 ], reported the fabrication of basic, acidic, and neutral titanate nanotubes (TNTs) by a hydrothermal method, and these materials were evaluated for the catalytic reduction of NO with ammonia. Manganese oxides were loaded to the three TNT formulations to yield Mn-doped titanate nanosheets, titanate nanorods, and titanate nanotubes (i.e., Mn/TNTs) in the case of basic, acidic, and neutral pH media, respectively.…”
Section: Inorganic Nanomaterialsmentioning
confidence: 99%